Contributions to the development of the piano sonata : the sonatas of Joseph Haydn, with special reference to their historic position and to the influence of German, Austrian and Italian elements on their form and style - Heuschneider, Karin (Rhodes University, Faculty of Humanities, Department of Music and Musicology, 1970)
This thesis, which is intended for inclusion in "The Piano Sonatas of the 18th century in Austria" (Vol.3 in the publication series "Contributions the the development of the Piano Sonata") aims to evaluate Haydn's position within the history of the piano sonata. In spite of the widespread popularity of Haydn's sonatas among professional musicians and amateurs, surprisingly little has yet been published regarding the compositional aspects of these works. The main contributions of musicological value were written by Hermann Abert, Karl Geiringer, Walter Georgii and William S.Newman. The recent studies, published as Vol.l and Vol.2 in the above mentioned series, made it possible to trace in much greater detail the various formative factors that influenced the form and style of Haydn's piano sonatas. Moreover, it proved the composer's personal merits not only in the development of this specific genre but also in the creation of 'The International Viennese Language of the High-Classical Period'. The newly gained insight, in turn, should lead to an even higher appreciation of the great master, who utilized the achievements of his predecessors and contemporaries in an original and individual manner and thereby gained a position far superior to that of many other composers.
Keywords: Haydn, Joseph, 1732-1809; Music -- History and criticism -- 18th century; Music, influence of -- Germany; Music, influence of -- Austria; Music, influence of -- Italy